About the reduction mechanism of friction and wear out in triboconjugation of «neck - coating - bearing - Кубич, В.И.; Ивщенко, Л.И. (Problems of Tribology, 2014)
Presented are the results of x-ray spectrum analysis of secondary structures formed by contact interaction of components of initial coating on necks and antifriction layer of bearing and produced products. Obtained data have completed notions about the composition and produced antifriction mechanical properties of secondary structures, being formed from the complex of materials: tin bronze БрОФ4-0,25; surface active medium %, (ат): gallium 81, indium 19 in triboconjugation of «neck - coating - bearing» that provided possibilities to reveal the reduction mechanism of friction and wear out in it.